2006
DOI: 10.1016/j.physd.2006.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of stochastic noise in the yeast galactose utilization pathway

Abstract: Genetic networks are often affected by stochastic noise, due to the low number of molecules taking part in certain reactions. In complex regulatory networks, noise in any one chemical species may induce noise in the rest of the system. In this paper, we analyse the sources of stochastic noise in the yeast galactose utilization pathway at the level of the complete system, by using both computer simulations, and experimental comparisons 2 between wild-type yeast and a modified strain. A computer model was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…We speculate that acting alone, Oaf1p-Pip2p-mediated expression is noisy because PIP2 mRNA has a high level of fluctuations in the model (as defined by the steady-state CV), and this variability is presumably due to the low copy number of PIP2 mRNA (see Data S1) and the fact that PIP2 is positively autoregulated. Previous studies have established that a low copy number of a gene's mRNA (34,35) and positive autoregulation of a gene (36) can both contribute to variations in the protein level, and, in the case of a TF, to increased variability of expression of downstream gene targets (extrinsic noise) (37). In the presence of Adr1p, this noise is expected to be buffered because of its direct regulatory influence on the target gene, which increases AOPY gene expression, thereby decreasing the relative variation in expression from the target.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that acting alone, Oaf1p-Pip2p-mediated expression is noisy because PIP2 mRNA has a high level of fluctuations in the model (as defined by the steady-state CV), and this variability is presumably due to the low copy number of PIP2 mRNA (see Data S1) and the fact that PIP2 is positively autoregulated. Previous studies have established that a low copy number of a gene's mRNA (34,35) and positive autoregulation of a gene (36) can both contribute to variations in the protein level, and, in the case of a TF, to increased variability of expression of downstream gene targets (extrinsic noise) (37). In the presence of Adr1p, this noise is expected to be buffered because of its direct regulatory influence on the target gene, which increases AOPY gene expression, thereby decreasing the relative variation in expression from the target.…”
Section: Discussionmentioning
confidence: 99%
“…Distributions of these two enzyme activities in the foliage provide state-dependent enzyme correlation as the consequence of the leaf sampling from various branches and places but in the same time. Distributions of these enzyme activities have been checked by Kolmogorov-Smirnov test [7]. This test did not contradict the assumption that these data might follow normal distribution.…”
Section: State-dependent Correlations Of Some Biochemical Variables Imentioning
confidence: 99%
“…To minimize the stochastic noise of gene expression there are specific mechanisms in the cell and this process in the yeast galactose utilization pathway have already been modelled [7]. Moreover, the biological noise has been established to have a regulatory role in the gene expression [8] too.…”
Section: Ranks Of the Values Of Variables {Rmentioning
confidence: 99%
“…However, given the nature of these alleles, it is not known if these polymorphisms are present in wild populations or are laboratory derived. Additional evidence comes from the study of the S. cerevisiae galactose regulon where it was found that genetic manipulation of the regulatory feedback loop could lead to increased stochastic noise in the network's output [30] , [31] . Genetic control of stochastic noise has also been identified using QTLs for yield stability in crops [32] and gene expression in 18 isogenic mouse lines [19] .…”
Section: Introductionmentioning
confidence: 99%